2022
DOI: 10.1186/s13643-022-01896-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators associated with the use of mental health services among immigrant students in high-income countries: a scoping review protocol

Abstract: Background While the mental health of immigrants is a growing issue that is attracting increasing interest from researchers, the same cannot be said for the mental health of immigrant students especially for international students. Indeed, the mental health of immigrant students and their use of mental health services are still poorly documented despite the significant increase in the number of these students in many high-income countries. This scoping review aims to providing an overview and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A strength of this review is that we followed a predefined protocol [ 36 ] that enabled a well-structured, rigorous, and systematic approach in arriving at results. Additionally, based on a set of predefined eligibility criteria studies were carefully selected and have yielded potentially useful information regarding the barriers and facilitators of mental health services among immigrant students in high income countries.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of this review is that we followed a predefined protocol [ 36 ] that enabled a well-structured, rigorous, and systematic approach in arriving at results. Additionally, based on a set of predefined eligibility criteria studies were carefully selected and have yielded potentially useful information regarding the barriers and facilitators of mental health services among immigrant students in high income countries.…”
Section: Discussionmentioning
confidence: 99%
“…50 On the contrary, possession of adequate mental health literacy served as a facilitator for accessing MHS. 51 Table 6 Relationship between older adults' perceived mental health distress as an impact of the COVID-19 pandemic and the sociodemographic, clinical characteristics, knowledge, familiarity, and barriers to seeking mental health services Items Perceived mental health distress as an impact of the COVID-19 pandemic. The COVID-19 pandemic stimulated the revolutionary spread and utilization of online health services and telemedicine as a reliable alternative for on-site clinical interviewing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, limited knowledge of extant services and how to find them can delay the care or break the continuity of receiving it 50 . On the contrary, possession of adequate mental health literacy served as a facilitator for accessing MHS 51 …”
Section: Discussionmentioning
confidence: 99%
“…Hirai et al 32 suggested that positive attitudes toward treatment by family members or partners and encouragement to seek mental health care from close relatives may have a positive impact on patients' chances of receiving mental health care. [33][34][35][36][37][38] For example, a family member or partner who discovers self-injury or trauma recommends that the patient could visit an emergency room, and the physician refers the patient to a psychiatrist; thus, witnessing self-injury may lead to medical support for the patient. The middle-aged group was recorded as having a higher history of psychiatric consultation than other age groups.…”
Section: Breakdown Of Suicide Deaths In This Studymentioning
confidence: 99%